The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3390/md11041104
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Structure Elucidation of Three New Dolastanes from the Brown Alga Dilophus spiralis

Abstract: Three new dolastane diterpenes (1–3) and five previously reported perhydroazulenes were isolated from the organic extracts of the brown alga Dilophus spiralis. The structure elucidation and the assignment of the relative configurations of the isolated natural products were based on extensive analyses of their spectroscopic data, whereas the absolute configuration of metabolite 2 was determined through its chemical conversion to a previously isolated compound of known configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
(17 reference statements)
0
10
0
Order By: Relevance
“…The absolute congurations of 517 and 519 were assumed on the basis of biogenetic considerations. 530 The cytotoxic meronorsesquiterpenoids cystoazorone A 520 and B 521 and meroditerpenoids cystoazorol A 522 and B 523 were isolated from Cystoseira abies-marina (Mosteiros, Sao Miguel Is., Azores) 531 while a series of meroditerpenoids cystodione A-F 524-529, all with strong antioxidant properties in the ABTS assay, were isolated from Cystoseira usneoides (Gibraltar Strait). 532 The mildly antiproliferative meroditerpenoid zonaquinone acetate 530 was obtained from a Jamaican Stypopodium zonale.…”
Section: Brown Algaementioning
confidence: 99%
“…The absolute congurations of 517 and 519 were assumed on the basis of biogenetic considerations. 530 The cytotoxic meronorsesquiterpenoids cystoazorone A 520 and B 521 and meroditerpenoids cystoazorol A 522 and B 523 were isolated from Cystoseira abies-marina (Mosteiros, Sao Miguel Is., Azores) 531 while a series of meroditerpenoids cystodione A-F 524-529, all with strong antioxidant properties in the ABTS assay, were isolated from Cystoseira usneoides (Gibraltar Strait). 532 The mildly antiproliferative meroditerpenoid zonaquinone acetate 530 was obtained from a Jamaican Stypopodium zonale.…”
Section: Brown Algaementioning
confidence: 99%
“…17 Two compounds are also isolated from the brown alga D. spiralis collected from Elafonissos Island, Greece. 28 Compound 29 exhibits moderate cytotoxicity against hepatoma (HepG2), fibroblast (WI-38), African green monkey kidney (VERO), and breast cancer cells (MCF-7) with IC 50 29 Compounds 29 and 30 display potent antithrombotic activity against thrombin with 50% inhibition at 0.68 mM. 30 Compound 29 displays remarkable antifouling activity against the invasive freshwater mussel Limnoperna fortunei at the concentration of 4.7 µg/cm 2 .…”
Section: Prenylated-guaiane Diterpenesmentioning
confidence: 99%
“…40 A prenylated-guaiane diterpene, named dictytriene B (35), is obtained from the brown alga D. spiralis collected from Elafonissos Island, Greece. 28 Other Diterpenes of Group I Four prenylated-bicyclogermacrane diterpenes, compounds (36)(37)(38)(39), are separated from the brown alga Dilophus prolificans collected from the New South Wales coast near Sydney, Australia. 41 A prenylated-germacrane diterpene, named dilophol (40), is isolated from the brown alga D. ligulatus collected from the littoral zone of the east coast of Sicily (Porto Palo), Italy.…”
Section: Prenylated-guaiane Diterpenesmentioning
confidence: 99%
“…Analysis of the presented NMR data revealed a close alignment to the tricyclic dolastane skeleton, which appears to be a skeletal framework characteristic to this alga species [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. However, differences in the chemical shifts because of the oxygenation pattern suggested that compound 1 was a new natural product.…”
Section: Resultsmentioning
confidence: 99%
“…Marine algae of the order Dictyotales, (Phaeophyta) have been found to be distributed in tropical and sub-tropical waters. Chemical investigations have shown the order to be a rich source of monocyclic, bicyclic and tricyclic terpenes such as dolabellane, meroditerpenoid, dolastane and seco-dolastane skeleton types [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Quite a number of diterpenes belonging to the Dictyotaceae family, inhabitants of the Atlantic and Indian Oceans, belong to the dolastane and seco-dolastane types.…”
Section: Introductionmentioning
confidence: 99%